Geopolitical fault-line cities in the world of divided cities. (May 2019) - Gentile, Michael
Abstract: The literature on divided (or contested) cities has expanded rapidly during the past decade, with a handful of iconic sites presiding over the long list of cities wounded by conflict, violence or general unrest. In this article, it is suggested that this literature has overlooked a particular, and increasingly prominent, type of divided city deserving of attention in its own right: the geopolitical fault-line city. The main differences between the "classic" divided city and the geopolitical fault-line city relate to the character and origin of conflict. In divided cities, conflict is mostly local and related to social and spatial justice concerns, discrimination, security and political representation; this makes it somewhat predictable. In geopolitical fault-line cities, on the other hand, the main disputes are about geopolitical alignment, foreign policy, and the overall character of government; such disputes are largely scripted elsewhere, adding a substantial measure of volatility. This article's contribution lies in its provisional theorization of the geopolitical fault-line city in the light of the literature on divided cities. Against a background of powerful ongoing changes in the global information landscape – most notably the increased influence of social media – it illustrates the main characteristics of the geopolitical fault-line city, theorizing its distinctiveness as intrinsically related to the spatio-temporal evolution of information diffusion across the territories of antagonistically predisposed geopolitical alliances.